A case control study on s. uric acid and s. creatinine level in pre-eclampsia patients of a tertiary care hospital in Jabalpur district of Central India - Yadav, Bhagwan S.; Jain, Sharad K.; Toppo, Neelam A.; Dehariya, Chanchlesh (International Journal of Research in Medical Sciences, 2018)
Background: Pre-eclampsia is a multisystem disorder of pregnancy which is characterized by hypertension with proteinuria after 20 weeks of gestation in previously normotensive and non proteinuric pregnant women. Pre-eclampsia associated with intrauterine growth retardation, preterm birth, maternal and perinatal death. Serum creatinine and uric acid has been shown to play a significant role in the pathogenesis of the disease and often precede clinical manifestations. This study compares the serum creatinine and uric acid in pre -eclampsia case and normal pregnant women and to assess its role in pre-eclampsia. Methods: 158 patients of which 79 pre-eclampsia (cases) and 79 (controls) were selected randomly and were matched with their gestational age in patient who Attending ANC clinic at Department of Obstretics and Gynecology in March 2016 to August 2017. Lipid profile was estimated by the Randox imola is a compact fully automated clinical chemistry analyser. Results: Authors observed that pre-eclampsia is more common in young age pregnant women with low socioeconomic status with strenuous activities. The mean age was 24.51±3.707 years. The mean serum creatinine and urice acid value is analysed in pre-eclampia cases and compared with control group showing significantly increase (p<0.0001). Conclusions: Young age, nullyparity, low socio economic status specially labour occupation, with derangment of Serum creatinine in pregnant women were found to be more prone to develop pre-eclampsia. Proper history tacking, examination and estimation of serum creatinine and uric acid may be helpful for early diagnosis and management of pre–eclampsia in order to prevent fetal and maternal complications especially in nulliparous women.